2020
DOI: 10.3389/fpsyt.2020.579057
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Representation of Depressive Symptoms and the Influence of Stigma in Arabic-Speaking Refugee Outpatients

Abstract: The number of distressed refugees from the Arab world is relatively high in Germany and other host countries worldwide. For this specific population, substantial challenges and barriers have already been identified that hamper access to Germany's health care system. This study aims to contribute to this line of research by exploring the representation of depressive symptoms, both somatic and psychological, in order to inform clinicians about the most prevalent symptoms reported by Arabic-speaking refugee outpa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
(132 reference statements)
2
3
0
Order By: Relevance
“…This seems to be robust and persistent over time, as self-stigma was higher in people with probable PTSD on all three measurements. This finding is in line with previously found associations between stigma and psychological symptoms (Byrow et al, 2019 ; Kira et al, 2015 ; Lindheimer et al, 2020 ; Livingston & Boyd, 2010 ) and supports the notion that stigma can be seen as a major mental health burden contributing to already existing mental illness (Kira et al, 2014 ). Moreover, since the SSOMI questionnaire asks hypothetical questions (‘if I had a mental illness’), the present results add that self-stigma in people with mental health burdens is even higher than people without mental illness expect it to be.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This seems to be robust and persistent over time, as self-stigma was higher in people with probable PTSD on all three measurements. This finding is in line with previously found associations between stigma and psychological symptoms (Byrow et al, 2019 ; Kira et al, 2015 ; Lindheimer et al, 2020 ; Livingston & Boyd, 2010 ) and supports the notion that stigma can be seen as a major mental health burden contributing to already existing mental illness (Kira et al, 2014 ). Moreover, since the SSOMI questionnaire asks hypothetical questions (‘if I had a mental illness’), the present results add that self-stigma in people with mental health burdens is even higher than people without mental illness expect it to be.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the majority of participants came from Syria (53.7%) and were male (72.4%). This distribution is similar to the general population of forcibly displaced people in Germany and common for current samples in this research area (Bär et al, 2021 ; Lindheimer et al, 2020 ). Even though, in the present sample and previous research (Livingston & Boyd, 2010 ), no gender differences in self-stigma were found, gender differences in help seeking are a common finding (Maguen et al, 2012 ; Marshall et al, 2006 ).…”
Section: Discussionsupporting
confidence: 82%
“…To our knowledge, our work is the first to apply the SSMIS-SF in a refugee sample and further evidence is needed in order to draw conclusions on the severity of mental health self-stigma in different refugee populations. Using the Brief Version of the Internalized Stigma of Mental Illness Scale (ISMI-10) (37), a recent study reported mild mental health selfstigma in a sample of Arabic-speaking (predominantly Syrian) refugee outpatients with depressive symptoms in Germany (38).…”
Section: Mental Health Self-stigma In the Sanadak Samplementioning
confidence: 99%
“…Stigma, in particular, can play an important role in the expression of psychological symptoms, as one study on depression in Arabic-speaking refugees revealed that the expression of psychological symptoms of depression, but not somatic ones, were associated with high levels of stigma 34 . This highlights the importance of socio-cultural contexts in shaping the expression of psychological symptoms.…”
Section: Discussionmentioning
confidence: 99%